Incidence of carditis and predictors of pacemaker implantation in patients hospitalized with Lyme disease - Uwajachukwumma A. Uzomah (Public Library of Science (PLoS), 2021)
Background Lyme carditis, defined as direct infection of cardiac tissue by Borrelia bacteria, affects up to 10% of patients with Lyme disease. The most frequently reported clinical manifestation of Lyme carditis is cardiac conduction system disease. The goal of this study was to identify the incidence and predictors of permanent pacemaker implantation in patients hospitalized with Lyme disease. Methods A retrospective cohort analysis of the Nationwide Inpatient sample was performed to identify patients hospitalized with Lyme disease in the US between 2003 and 2014. Patients with Lyme carditis were defined as those hospitalized with Lyme disease who also had cardiac conduction disease, acute myocarditis, or acute pericarditis. Patients who already had pacemaker implants at the time of hospitalization (N = 310) were excluded from the Lyme carditis subgroup. The primary study outcome was permanent pacemaker implantation. Secondary outcomes included temporary cardiac pacing, permanent pacemaker implant, and in-hospital mortality. Results Of the 96,140 patients hospitalized with Lyme disease during the study period, 10,465 (11%) presented with Lyme carditis. Cardiac conduction system disease was present in 9,729 (93%) of patients with Lyme carditis. Permanent pacemaker implantation was performed in 1,033 patients (1% of all Lyme hospitalizations and 11% of patients with Lyme carditis-associated conduction system disease). Predictors of permanent pacemaker implantation included older age (OR: 1.06 per 1 year; 95% CI:1.05–1.07; P<0.001), complete heart block (OR: 21.5; 95% CI: 12.9–35.7; P<0.001), and sinoatrial node dysfunction (OR: 16.8; 95% CI: 8.7–32.6; P<0.001). In-hospital mortality rate was higher in patients with Lyme carditis (1.5%) than in patients without Lyme carditis (0.5%). Conclusions Approximately 11% of patients hospitalized with Lyme disease present with carditis, primarily in the form of cardiac conduction system disease. In this 12-year study, 1% of all hospitalized patients and 11% of those with Lyme-associated cardiac conduction system disease underwent permanent pacemaker implantation.